Evaluation of Structural Condition of Flexible Pavement Using The AASHTO 1993 and The MEPDG 2008 Method (Case Study: Cipatujah-Kalapagenep-Pangandaran National Road) : Evaluation of Structural Condition of Flexible Pavement Using The Asshto 1993 and the MEPDG 2008 Method (Case Study: Cipatujah-Kalapagenep-Pangandaran National Road Section) - Retna Ayu Kirana Djuhana; Bambang Sugeng Subagio; Aine Kusumawati (Jurnal Teknik Sipil, 2021)
Abstract Flexible pavement on Cipatujah-Kalapagenep-Pangandaran National Road has a structural damage which marked by potholes and cracks on the pavement caused by excessive load trucks, so the pavement needs an overlay to improve the pavement condition. This analysis using AASHTO 1993 and MEPDG 2008 method. These methods used because the MEPDG 2008 was developed from AASHTO 1993 method, so the output will be more economic. But, the MEPDG 2008 has not applied yet in Indonesia, so the method will be studied to determine the method feasibility to be applied in Indonesia. This research was analyzed with two skenarios of CESAL, four trial thicknesses, and three CBR numbers. The overlay thickness value using the AASHTO 1993 was at 10 cm and 11 cm for scenario 1 and 2, while the overlay thickness using the MEPDG 2008 was at 10 cm for the two scenarios. The result from AASHTO 1993 was chosen because the MEPDG 2008 needs to studied further yet about suitable calibration factor for Indonesian pavement condition. The cause of difference result are structural damage assessment for AASHTO 1993 method based on deflection value from FWD while MEPDG 2008 method based on stresses and strains respond, material characteristics, and local calibration.   Keywords: AASHTO 1993, MEPDG 2008, stress and strain response, FWD deflection value, local calibration factors, overlay thickness. Abstrak Perkerasan lentur jalan Nasional Cipatujah-Kalapagenep-Pangandaran mengalami kerusakan struktural yang ditandai dengan lubang dan retak pada perkerasan badan jalan yang disebabkan oleh truk pengangkut pasir yang memiliki beban berlebih, sehingga diperlukan penambahan tebal lapis tambah pada perkerasan jalan eksisting untuk mengembalikan kondisi kemantapan jalan. Dalam penelitian ini dilakukan analisis terhadap kondisi struktural perkerasan jalan lentur eksisting menggunakan Metoda AASHTO 1993 dan Metoda MEPDG 2008 dengan pertimbangan bahwa MEPDG 2008 merupakan pengembangan dari AASHTO 1993. Namun, Metoda MEPDG 2008 belum diterapkan di Indonesia, maka perlu dilakukan kajian awal untuk mengetahui kelayakan metoda tersebut diterapkan di Indonesia. Analisis ini menggunakan dua skenario nilai CESAL, empat macam tebal dan tiga macam nilai CBR. Berdasarkan hasil analisis, diperoleh tebal overlay menggunakan metoda AASHTO 1993 sebesar 10 cm dan 11 cm untuk skenario 1 dan 2, sedangkan tebal overlay menggunakan metoda MEPDG 2008 diperoleh tebal overlay sebesar 10 cm untuk kedua skenario. Namun dalam penelitian ini dipilih hasil dari metoda AASHTO 1993 dikarenakan MEPDG 2008 masih memerlukan kajian lanjut terkait faktor kalibrasi berdasarkan kondisi perkerasan di Indonesia. Dari penelitian diketahui faktor yang menyebabkan perbedaan hasil adalah Metoda AASHTO 1993 berdasarkan nilai lendutan FWD, sedangkan MEPDG 2008 berdasarkan respon tegangan dan regangan, karakteristik material, dan kalibrasi lokal. Kata-kata kunci: AASHTO 1993, MEPDG 2008, respon tegangan dan regangan, nilai defleksi FWD, faktor kalibrasi lokal, ketebalan lapisan.